How Do Amusement, Anger and Fear Influence Heart Rate and Heart Rate Variability? - Wu, Yan; Gu, Ruolei; Yang, Qiwei; Luo, Yue-jia (Frontiers in Neuroscience, 2019)
Emotions involve subjective experiences, behavioral performances, and physiological responses. Research concerning autonomic states corresponding to different emotions has prevailed for several decades. The present study was designed to investigate how specific emotions influence cardiac activities that reflect autonomic responses. Affective videos selected from a standardized Chinese database were used to induce amused, fearful, angry, and neutral emotions, while electrocardiogram and self-rated emotional experiences were recorded. Heart rate was significantly lower in the amused condition than in the angry, fearful and neutral condition. There were no significant differences among the latter three conditions. The root mean square of successive differences, an index of heart rate variability (HRV), was significantly larger in the amused condition than in the fearful, neutral, and angry conditions. It was also significantly larger in the angry condition than in the fearful condition. There were no significant differences between the fearful and neutral, or angry and neutral conditions. These results revealed that: (1) amusement activates the parasympathetic nervous system, and (2) compared with fear, anger is more likely to be linked with parasympathetic activation. We suggest that HRV, rather than the valence dimension (i.e., positive or negative) be regarded as a potential index to discriminate emotions related to approach or avoidance motivation.